The Effectiveness of Mindfulness-Based Therapy in Improving Well-Being: Autism Spectrum Disorder (ASD): A Systematic Literature Review - Meza Saputri; Nono Hery Yoenanto; Wiwin Hendriani; Pramesti Pradna Paramita (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to systematically review the effectiveness of mindfulness-based therapy in improving the well-being of children with autism spectrum disorder (ASD) through a Systematic Literature Review (SLR) approach. Articles were collected from the Scopus database using the keywords “autism spectrum disorder AND mindfulness,” “Mindfulness-Based Therapy AND Autism,” and “Mindfulness Intervention AND Autism.” The selection process followed the PRISMA guidelines, with inclusion criteria comprising quantitative studies with an experimental design involving mindfulness interventions for individuals with ASD, while exclusion criteria included non-empirical or qualitative-based research. The results indicate that mindfulness interventions, such as MBSR and Mymind, are effective in improving emotional regulation, reducing stress, enhancing social skills, and improving executive function and brain activity in children with ASD. Interventions involving families also strengthen the positive effects of therapy. These findings contribute to the development of psychological interventions that can support their application in clinical and special education settings, with recommendations for further research using randomized controlled trial (RCT) designs with a multilevel and collaborative approach across educational and clinical settings to test the long-term effectiveness of mindfulness, preferably with a sufficient number of participants to generalize the research findings.